Pressure-sensitive adhesive layer, pressure-sensitive adhesive film, and optical film with pressure-sensitive adhesive layer

JP7629492B2Active Publication Date: 2025-02-13ZACROS CORP
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2023135617
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-02-13
Estimated Expiration
2034-01-27

AI Technical Summary

Benefits of technology

【0020】 本発明によれば、従来の要求事項および問題を克服して、厚さ1μm~20μmの薄膜にも拘わらず、高粘着力、高密着性の性能を有する粘着剤層、及びそれを用いた粘着フィルムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629492000001
    Figure 0007629492000001
  • Figure 0007629492000002
    Figure 0007629492000002
  • Figure 0007629492000003
    Figure 0007629492000003
Patent Text Reader

Abstract

To provide an adhesive layer, an adhesive film and an optical film with the adhesive layer which have both high adhesive strength and high adhesion performance in spite of being a thin film having a thickness of 1 μm to 20 μm.SOLUTION: There is provided an adhesive layer obtained by crosslinking an adhesive composition, wherein an acrylic polymer is a copolymer having a weight average molecular weight of 200000 to 2000000 obtained by copolymerizing (A) an alkyl (meth)acrylate monomer having an alkyl group having 1 to 14 carbon atoms, (B) a (meth)acrylate monomer having an aromatic group, (C) a vinyl monomer having a nitrogen atom, and (D) a copolymerizable vinyl monomer having a hydroxyl group without containing a copolymerizable vinyl monomer having a carboxyl group; a crosslinking agent is a tri-functional isocyanate compound; the thickness of the adhesive layer is 1 to 20 μm; the initial adhesive strength at a thickness of 20 μm is 3.0 N / 25 mm or more; the refractive index is 1.47 to 1.50; and the gel fraction is 50 to 70%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive layer and a pressure-sensitive adhesive film used for bonding between layers of optical components, etc. More specifically, the present invention relates to a pressure-sensitive adhesive layer having high adhesive strength and high adhesion performance despite being a thin film having a thickness of 1 μm to 20 μm, and a pressure-sensitive adhesive film using the same. [Background technology]

[0002] 2. Description of the Related Art Various pressure-sensitive adhesive films have been proposed for bonding optical members such as polarizing plates and retardation plates to adherends such as liquid crystal cells via pressure-sensitive adhesive layers (see, for example, Patent Documents 1 and 2). Patent Document 1 describes an optical pressure-sensitive adhesive composition that contains butyl acrylate or the like as a main monomer component and also contains an acrylamide compound or the like. Patent Document 2 describes an optical pressure-sensitive adhesive composition containing a (meth)acrylate having an alkyl group with 4 to 8 carbon atoms as a main component monomer, a monomer having a carboxyl group, and a vinyl monomer having a nitrogen atom. Furthermore, various pressure-sensitive adhesive films have been proposed that have been devised to increase the refractive index of the pressure-sensitive adhesive layer (see, for example, Patent Documents 3 to 8). Patent Document 3 describes an optical pressure-sensitive adhesive composition that contains a tackifier having an aromatic ring and a refractive index of 1.51 to 1.75. Patent Document 4 describes a pressure-sensitive adhesive sheet containing a pressure-sensitive adhesive composition that includes a copolymerizable polymer of an acrylic acid-modified monomer having an aromatic ring. Patent Document 5 describes an optical pressure-sensitive adhesive composition containing a tackifier resin having an aromatic ring and an aromatic phosphate ester plasticizer. Patent Document 6 describes a pressure-sensitive adhesive obtained by curing a pressure-sensitive adhesive composition containing an acrylic resin and an aromatic compound having one ethylenically unsaturated group. Patent Document 7 describes an optical component in which a retardation film and a birefringent plate are fixed to each other via an acrylic adhesive containing an aromatic monomer. Patent Document 8 describes a pressure-sensitive adhesive composition containing a urethane resin obtained by reacting an aromatic diisocyanate with an aromatic polyester diol. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-177022 A [Patent Document 2] JP 2012-201734 A [Patent Document 3] JP 2007-084762 A [Patent Document 4] JP 2011-153169 A [Patent Document 5] JP 2012-167188 A [Patent Document 6] JP 2012-021148 A [Patent Document 7] JP 2006-293281 A [Patent Document 8] JP 2009-091522 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, there has been a demand for adhesive films used to bond layers of optical components together, with the adhesive layer having a thickness of 20 μm or less in order to facilitate the thinning of optical components. Generally, the adhesive strength of a pressure-sensitive adhesive layer is approximately proportional to the thickness of the pressure-sensitive adhesive layer, and therefore, when the thickness of the pressure-sensitive adhesive layer is reduced, the adhesive strength decreases accordingly.

[0005] However, in recent years, adhesive films have been required to have adhesive strength equivalent to that of conventional adhesive films (with thick adhesive layers of approximately 30 μm) even when the thickness of the adhesive layer is reduced, and also to have durability equivalent to or greater than that of conventional adhesive films when left in high temperature and high humidity environments for long periods of time. Furthermore, because it is possible to make the adhesive layer thinner and to form an adhesive layer that does not require aging treatment (curing at a constant temperature), there is a demand for an NCF (Non Carrier Film) configuration consisting of only the adhesive layer, omitting the adhesive film substrate, and having a component structure of "release film / adhesive layer / release film."

[0006] Furthermore, in conventional pressure-sensitive adhesive films, an aging treatment is carried out after the pressure-sensitive adhesive film is attached to an adherend, which makes it possible to improve the adhesion between the adherend and the pressure-sensitive adhesive layer. However, in the case of NCF-type PSA films, the adhesive layer has already been aged, so the adhesive strength between the adherend and the adhesive layer is insufficient, and therefore there is a problem in that the surface of the adherend needs to be subjected to a surface treatment such as a corona treatment. What is needed is a self-adhesive film that overcomes these requirements and problems.

[0007] The present invention has been made in consideration of the above circumstances, and has an objective of providing an adhesive layer that has high adhesive strength and high adhesion properties despite being a thin film having a thickness of 1 μm to 20 μm, and an adhesive film using the same. [Means for solving the problem]

[0008] In order to solve the above problems, the technical idea of ​​the present invention is to provide an adhesive layer formed by crosslinking an adhesive composition made of an acrylic polymer, in which at least one alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14 is used as a main monomer, and at least one vinyl monomer having a copolymerizable nitrogen atom is contained as another copolymerizable monomer, and by copolymerizing and crosslinking, a pressure-sensitive adhesive layer having both strong adhesive strength and high adhesion properties is obtained.

[0009] Further, in order to solve the above-mentioned problems, the present invention provides a pressure-sensitive adhesive layer obtained by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer and a crosslinking agent, the acrylic polymer being copolymerized with 2 to 50 parts by weight of (C) a combination of at least one or more vinyl monomers having no hydroxyl group or carboxyl group and having a nitrogen atom, and 0.1 to 10 parts by weight of (D) a combination of at least one or more copolymerizable vinyl monomers having a hydroxyl group, as other copolymerizable monomers, relative to 100 parts by weight of a total of 70 to 95 parts by weight of at least one or more alkyl (meth)acrylate monomers having an alkyl group of C1 to C14 carbon atoms and (B) 5 to 30 parts by weight of at least one or more (meth)acrylate monomers having an aromatic group, without containing a copolymerizable vinyl monomer having a carboxyl group. the (C) vinyl monomer having no hydroxyl group or carboxyl group and having a nitrogen atom is at least one compound selected from the group consisting of N-vinylpyrrolidone, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-dibutyl(meth)acrylamide, N,N-diethylaminopropyl(meth)acrylamide, N,N-dimethylaminoethyl(meth)acrylamide and N-vinylcaprolactam; the crosslinking agent is a trifunctional isocyanate compound; the pressure-sensitive adhesive layer has a thickness of 1 μm to 20 μm and a refractive index of 1.47 to 1.50.

[0010] In addition, when the thickness of the pressure-sensitive adhesive layer is 20 μm, the initial adhesive strength after lamination is preferably 3.0 (N / 25 mm) or more.

[0011] The pressure-sensitive adhesive composition preferably contains an antistatic agent.

[0012] The antistatic agent is preferably an ionic compound having a melting point of 25 to 50°C.

[0013] The pressure-sensitive adhesive composition contains 0.1 to 5.0 parts by weight of an ionic compound having a melting point of 25 to 50° C., and the surface resistivity of the pressure-sensitive adhesive layer is 5.0×10 +10 It is preferable that the resistance is Ω / □ or less.

[0014] The present invention also provides a pressure-sensitive adhesive film, characterized in that the pressure-sensitive adhesive layer is formed on one side of a release film, and has a structure of release film / pressure-sensitive adhesive layer / release film.

[0015] The present invention also provides a pressure-sensitive adhesive film comprising the pressure-sensitive adhesive layer laminated on one surface of a substrate.

[0016] The present invention also provides a film that uses the pressure-sensitive adhesive film and is used for bonding a polarizing plate and a display panel.

[0017] The present invention also provides a film for a touch panel, which uses the pressure-sensitive adhesive film.

[0018] The present invention also provides a film for electronic paper, which uses the pressure-sensitive adhesive film.

[0019] The present invention also provides a pressure-sensitive adhesive layer-attached optical film, comprising an optical film and the pressure-sensitive adhesive layer laminated on at least one surface of the optical film. Effect of the Invention

[0020] According to the present invention, it is possible to overcome the conventional requirements and problems and provide an adhesive layer having high adhesive strength and high adhesion performance despite being a thin film having a thickness of 1 μm to 20 μm, and an adhesive film using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will be described below based on preferred embodiments. The pressure-sensitive adhesive layer of the present invention is characterized in that, in the pressure-sensitive adhesive layer obtained by crosslinking a pressure-sensitive adhesive composition made of an acrylic polymer, the acrylic polymer is a copolymer containing, as a main component (meth)acrylate monomer, at least one alkyl (meth)acrylate monomer having a carbon number of C1 to C14 in the alkyl group and at least one (meth)acrylate monomer having an aromatic group, and containing, as other copolymerizable monomers, at least one vinyl monomer having a nitrogen atom and at least one copolymerizable vinyl monomer having a hydroxyl group, a crosslinking agent that crosslinks the pressure-sensitive adhesive composition is a trifunctional isocyanate compound, the pressure-sensitive adhesive layer has a thickness of 1 μm to 20 μm, and at a thickness of 20 μm, the initial adhesive strength of the laminate is 3.0 (N / 25 mm) or more, and the refractive index is 1.47 to 1.50. In this specification, the statement that an acrylic polymer (copolymer) contains (contains) a monomer means that the monomer is mainly copolymerized in the acrylic polymer (copolymer), but does not exclude the case where a part of the raw material monomer remains unreacted in the acrylic polymer (copolymer).

[0022] Examples of the alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14 include at least one of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, cyclopentyl (meth)acrylate, and cyclohexyl (meth)acrylate. The alkyl group of the alkyl (meth)acrylate monomer may be linear, branched, or cyclic. The proportion of (A) alkyl (meth)acrylate monomer having an alkyl group carbon number of C1 to C14 per 100 parts by weight of the combined total of (A) and (B) (meth)acrylate monomer having an aromatic group is preferably 70 to 95 parts by weight.

[0023] Examples of the (meth)acrylate monomer having an aromatic group include benzyl (meth)acrylate, naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxybutyl (meth)acrylate, 2-(1-naphthyloxy)ethyl (meth)acrylate, 2-(2-naphthyloxy)ethyl (meth)acrylate, 6-(1-naphthyloxy)hexyl (meth)acrylate, 6-(2-naphthyloxy)hexyl (meth)acrylate, 8-(1-naphthyloxy)octyl (meth)acrylate, 8-(2-naphthyloxy)octyl (meth)acrylate, ethylene glycol o-phenylphenyl ether (meth)acrylate, and polyethylene glycol o-phenylphenyl ether (meth)acrylate. In order to obtain a pressure-sensitive adhesive layer having a high refractive index, it is preferable to blend at least one or more (meth)acrylate monomers having an aromatic group. By mixing these (meth)acrylate monomers having aromatic groups with alkyl (meth)acrylate monomers, which are the main component monomers, having an alkyl group with a carbon number of C1 to C14, the refractive index of the obtained pressure-sensitive adhesive layer can be increased and adjusted, and the refractive index difference between optical components can be reduced, thereby reducing total reflection and improving the total light transmittance. In addition, in the pressure-sensitive adhesive layer of the present invention, (B) the (meth)acrylate monomer having an aromatic group is preferably contained in a proportion of 5 to 30 parts by weight out of 100 parts by weight of the (meth)acrylate monomer which is the main component consisting of (A) and (B) combined.

[0024] Examples of vinyl monomers having a nitrogen atom include cyclic nitrogen vinyl compounds such as N-vinylpyrrolidone, N-vinylcaprolactam, and (meth)acryloylmorpholine; dialkyl-substituted (meth)acrylamides such as N-ethyl-N-methyl(meth)acrylamide, N-methyl-N-propyl(meth)acrylamide, N-methyl-N-isopropyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-dibutyl(meth)acrylamide; N-ethyl-N-methylaminoethyl(meth)acrylate, N-methyl-N-propylaminoethyl(meth)acrylate, N-methyl-N-isopropylaminoethyl(meth)acrylate, N,N-dimethylaminomethyl(meth)acrylate, and N,N-dimethylaminoethyl(meth)acrylamide; ) acrylate, dialkylamino (meth)acrylate such as N,N-dimethylaminopropyl (meth)acrylate, N,N-dimethylaminobutyl (meth)acrylate, N,N-dipropylaminoethyl (meth)acrylate, and N,N-dibutylaminoethyl (meth)acrylate; dialkyl-substituted aminoalkyl (meth)acrylamides such as N-ethyl-N-methylaminopropyl (meth)acrylamide, N-methyl-N-propylaminopropyl (meth)acrylamide, N-methyl-N-isopropylaminopropyl (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylamide, N,N-diethylaminopropyl (meth)acrylamide, N,N-dipropylaminopropyl (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylamide, and N,N-diethylaminoethyl (meth)acrylamide, and the like.

[0025] The vinyl monomer having a nitrogen atom is preferably one having no hydroxyl group, more preferably one having no hydroxyl group or carboxyl group, so as to be distinguishable from the compound (D) described later.As such a monomer, the monomers exemplified above, for example, acrylic monomers having N,N-dialkyl-substituted amino group or N,N-dialkyl-substituted amide group; N-vinyl-substituted lactams such as N-vinylpyrrolidone and N-vinylcaprolactam; N-(meth)acryloyl-substituted cyclic amines such as N-(meth)acryloylmorpholine are preferred.

[0026] In the pressure-sensitive adhesive layer according to the present invention, the vinyl monomer having a nitrogen atom contained in the acrylic polymer of the pressure-sensitive adhesive composition can impart the necessary adhesive strength and durability to the pressure-sensitive adhesive layer. In the pressure-sensitive adhesive layer according to the present invention, the vinyl monomer having a nitrogen atom contained in the acrylic polymer of the pressure-sensitive adhesive composition is preferably 2 to 50 parts by weight per 100 parts by weight of the (meth)acrylate monomer, which is the main component consisting of the combined components (A) and (B). In the pressure-sensitive adhesive layer of the present invention, examples of vinyl monomers having a nitrogen atom to be contained in the acrylic polymer of the pressure-sensitive adhesive composition that can be particularly preferably used include N-vinylpyrrolidone, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-dibutyl(meth)acrylamide, N,N-dimethylaminopropyl(meth)acrylamide, N,N-diethylaminopropyl(meth)acrylamide, N,N-dimethylaminoethyl(meth)acrylamide, and N-vinylcaprolactam.

[0027] Examples of copolymerizable vinyl monomers having a hydroxyl group (monomers having a hydroxyl group) include at least one of hydroxyalkyl (meth)acrylates such as 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and hydroxyethyl (meth)acrylate; and (meth)acrylamides having a hydroxyl group such as N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide. In addition, in the pressure-sensitive adhesive layer according to the present invention, the monomer having a hydroxyl group contained in the acrylic polymer of the pressure-sensitive adhesive composition can be used as a copolymerizable monomer for reducing the content of the monomer having a carboxyl group, which is considered to affect the corrosiveness of the resulting pressure-sensitive adhesive layer against a corrodible adherend such as the ITO surface of a transparent conductive film. Therefore, the monomer having a hydroxyl group can be used to improve the adhesive strength of the pressure-sensitive adhesive layer and reduce the corrosiveness. In the pressure-sensitive adhesive layer according to the present invention, the monomer having a hydroxyl group contained in the acrylic polymer of the pressure-sensitive adhesive composition is preferably 0.1 to 10 parts by weight per 100 parts by weight of the (meth)acrylate monomer, which is the main component consisting of the (A) and (B) combined.

[0028] The copolymer of the adhesive composition used in the adhesive layer of the present invention preferably comprises 100 parts by weight of a combination of 70 to 95 parts by weight of (A) at least one alkyl (meth)acrylate monomer having a carbon number of C1 to C14 in the alkyl group and 5 to 30 parts by weight of (B) at least one (meth)acrylate monomer having an aromatic group, 2 to 50 parts by weight of (C) at least one vinyl monomer having a nitrogen atom, and 0.1 to 10 parts by weight of (D) at least one copolymerizable vinyl monomer having a hydroxyl group. It is also preferable that the acrylic polymer does not contain a copolymerizable vinyl monomer having a carboxyl group as a monomer, since if the polymer has a carboxyl group, it may corrode an adherend such as ITO due to acid.

[0029] The polymerization method for the copolymer is not particularly limited, and any known polymerization method can be used as appropriate, such as solution polymerization, emulsion polymerization, etc. The weight average molecular weight of the copolymer is preferably 200,000 to 2,000,000. The copolymer is preferably an acrylic polymer, and preferably contains 50 to 100% by weight of an acrylic monomer such as a (meth)acrylic acid ester monomer or a (meth)acrylamide. The pressure-sensitive adhesive layer preferably has a gel fraction of 50 to 70%.

[0030] The properties of the pressure-sensitive adhesive composition, such as required physical properties, can be adjusted by blending the copolymer with a crosslinking agent and / or any suitable additives. As the crosslinking agent, for example, biuret modified products or isocyanurate modified products of diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, etc., and adducts with trivalent or higher polyols such as trimethylolpropane and glycerin are preferred. (E) Trifunctional isocyanate compounds.

[0031] The trifunctional isocyanate compound is preferably at least one selected from the group consisting of an isocyanurate of a hexamethylene diisocyanate compound, an isocyanurate of an isophorone diisocyanate compound, an adduct of a hexamethylene diisocyanate compound, an adduct of an isophorone diisocyanate compound, a biuret of a hexamethylene diisocyanate compound, a biuret of an isophorone diisocyanate compound, an isocyanurate of a tolylene diisocyanate compound, an isocyanurate of a xylylene diisocyanate compound, an isocyanurate of a hydrogenated xylylene diisocyanate compound, an adduct of a tolylene diisocyanate compound, an adduct of a xylylene diisocyanate compound, and an adduct of a hydrogenated xylylene diisocyanate compound.

[0032] When the copolymer is crosslinked using a trifunctional isocyanate compound, it is preferable that the copolymer has a functional group (particularly a hydroxyl group) capable of crosslinking with the crosslinking agent, and it is preferable that the copolymer contains a monomer having such a functional group in a side chain. It is also preferable that the pressure-sensitive adhesive composition contains 0.001 to 1 part by weight of a trifunctional isocyanate compound (E) as a crosslinking agent. The weight parts are the same as those of (A) to (D) in the copolymer.

[0033] The pressure-sensitive adhesive composition of the present invention may contain an antistatic agent to impart antistatic properties. The antistatic agent is preferably solid at room temperature (e.g., 25° C.), and more specifically, the antistatic agent is an ionic compound having a melting point of 25 to 50° C. The antistatic agent may be a quaternary ammonium salt type ionic compound having an acryloyl group. These antistatic agents are presumed to have a high affinity with acrylic polymers because they have a low melting point and contain long-chain alkyl groups. When antistatic properties are imparted, the surface resistivity of the pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition is 5.0×10 +10 It is preferable that the resistance is Ω / □ or less.

[0034] The antistatic agent, which is an ionic compound having a melting point of 25 to 50°C, is an ionic compound having a cation and an anion, in which the cation is a nitrogen-containing onium cation such as a pyridinium cation, an imidazolium cation, a pyrimidinium cation, a pyrazolium cation, a pyrrolidinium cation, or an ammonium cation, a phosphonium cation, or a sulfonium cation, and the anion is a hexafluorophosphate (PF 6 - ), thiocyanate (SCN - ), alkylbenzene sulfonate (RC 6 H 4 SO 3 - ), perchlorate (ClO 4 - ), tetrafluoroborate (BF 4 - ) and other inorganic or organic anion compounds. By selecting the chain length of the alkyl group, the position and number of the substituents, and other factors, it is possible to obtain compounds having a melting point of 25 to 50°C. The cation is preferably a quaternary nitrogen-containing onium cation, and examples thereof include quaternary pyridinium cations such as 1-alkylpyridinium (wherein the carbon atoms at positions 2 to 6 may be substituted or unsubstituted), quaternary imidazolium cations such as 1,3-dialkylimidazolium (wherein the carbon atoms at positions 2, 4, and 5 may be substituted or unsubstituted), and quaternary ammonium cations such as tetraalkylammonium.

[0035] The quaternary ammonium salt type ionic compound having an acryloyl group is an ionic compound having a cation and an anion, the cation being (meth)acryloyloxyalkyltrialkylammonium [R 3 N + -C n H 2n -OCOCQ=CH 2 , where Q=H or CH 3 , R = alkyl], and the anion is hexafluorophosphate (PF 6 - ), thiocyanate (SCN -), organic sulfonates (RSO 3 - ), perchlorate (ClO 4 - ), tetrafluoroborate (BF 4 - ), imide salts having fluorine atoms (R F 2 N - ) and other inorganic or organic anion compounds. F 2 N - )R F Examples of the imide salt having a fluorine atom include bis(fluorosulfonyl)imide salts [(FSO 2 ) 2 N - 〕, bis(trifluoromethanesulfonyl)imide salt [(CF 3 SO 2 ) 2 N - 〕, bis(pentafluoroethanesulfonyl)imide salt〔(C 2 F 5 SO 2 ) 2 N - and the like.

[0036] The antistatic agent, which is an ionic compound having a melting point of 25 to 50° C., is not particularly limited. Specific examples of the ionic compound having a pyridinium cation and a melting point of 25 to 50° C. include 1-octylpyridinium dodecylbenzenesulfonate, 1-dodecylpyridinium thiocyanate, 3-methyl-1-dodecylpyridinium hexafluorophosphate, 1-dodecylpyridinium dodecylbenzenesulfonate, and 4-methyl-1-octylpyridinium hexafluorophosphate. Specific examples of the quaternary ammonium salt type ionic compound having an acryloyl group include dimethylaminomethyl (meth)acrylate hexafluorophosphate methyl salt [(CH 3 )3 N + CH 2 OCOCQ=CH 2 ·PF 6 - , where Q=H or CH 3 〕, dimethylaminoethyl (meth)acrylate bis(trifluoromethanesulfonyl)imide methyl salt〔(CH 3 ) 3 N + (CH 2 ) 2 OCOCQ=CH 2 ·(CF 3 SO 2 ) 2 N - , where Q=H or CH 3 〕, dimethylaminomethyl (meth)acrylate bis(fluorosulfonyl)imide methyl salt〔(CH 3 ) 3 N + CH 2 OCOCQ=CH 2 ·(FSO 2 ) 2 N - , where Q=H or CH 3 ] etc. The ionic compound having a melting point of 25 to 50° C. is preferably contained in an amount of 0.1 to 5.0 parts by weight per 100 parts by weight of the (meth)acrylate monomer which is the main component consisting of the combined components (A) and (B).

[0037] When the pressure-sensitive adhesive composition of the present invention is used for bonding optical members to display panels or the like, it is preferable to add a silane coupling agent. Examples of the silane coupling agent to be added include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, vinyltriacetoxysilane, 3-acryloxypropyltrimethoxysilane, 3-acryloxypropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and the like. Examples of the silane coupling agent include silane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, vinyltrichlorosilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, etc. These silane coupling agents can be used alone or in combination of two or more, and the amount of the silane coupling agent added is preferably 0.001 to 5 parts by weight per 100 parts by weight of the adhesive composition.

[0038] As other optional components, known additives such as antioxidants, surfactants, curing accelerators, plasticizers, fillers, crosslinking catalysts, crosslinking retarders, curing retarders, processing aids, and antiaging agents can be appropriately blended in. These may be used alone or in combination of two or more kinds.

[0039] The pressure-sensitive adhesive layer of the present invention can be obtained by applying the pressure-sensitive adhesive composition to a substrate or a release film, and then crosslinking the pressure-sensitive adhesive composition. When used for bonding between layers of optical components, the adhesive layer is desirably thin, and the thickness of the adhesive layer is preferably 1 μm to 20 μm. In general, the adhesive strength of the adhesive layer is approximately proportional to the thickness of the adhesive layer, and when the thickness is 20 μm, the initial adhesive strength after bonding is preferably 3.0 (N / 25 mm) or more. When the pressure-sensitive adhesive layer of the present invention is attached to an optical member such as a polarizing plate (polarizing film), the adhesive strength to the polarizing plate is preferably equal to or greater than the lower limit value described above. In general, polarizing films are mainly made of a film of polyvinyl alcohol (PVA) adsorbed with iodine, and have a protective layer of saponified triacetyl cellulose (TAC) or polyethylene terephthalate (PET) on the surface. Therefore, the adhesive layer of the present invention preferably has an adhesive strength to an adherend such as saponified triacetyl cellulose (TAC) or the like equal to or greater than the lower limit value described above.

[0040] When the pressure-sensitive adhesive layer according to the present invention is used for bonding between layers of optical members, it is desirable that the difference in refractive index between the pressure-sensitive adhesive layer and the optical member is as small as possible in order to reduce the reflection of light at the interface between the pressure-sensitive adhesive layer and the optical member. For this reason, the refractive index of the pressure-sensitive adhesive layer is preferably 1.47 to 1.50.

[0041] The pressure-sensitive adhesive film of the present invention can be produced by forming the pressure-sensitive adhesive layer of the present invention on one side of a substrate or a release film. As the base film used for forming the pressure-sensitive adhesive layer and the release film (separator) for protecting the adhesive surface, a resin film such as a polyester film can be used. The substrate film may be subjected to an antifouling treatment using a silicone-based or fluorine-based release agent or coating agent, or silica microparticles or the like, or an antistatic treatment by coating or kneading an antistatic agent, on the side opposite to the side on which the pressure-sensitive adhesive layer of the resin film is formed.

[0042] The surface of the release film that faces the adhesive surface of the adhesive layer is subjected to a release treatment using a silicone-based or fluorine-based release agent. A "release film / adhesive layer / release film" configuration can be achieved by combining the release-treated surfaces of a release film on both sides of a single adhesive layer. In this case, the release films on both sides are peeled off sequentially or simultaneously to expose the adhesive surface, making it possible to attach it to an optical component such as an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films.

[0043] The pressure-sensitive adhesive film of the present invention can be used to bond a polarizing plate to a display panel. Examples of the display panel include, but are not limited to, a liquid crystal display device and an organic EL display. In addition, the adhesive film of the present invention can be used to bond various optical films for peripheral components of liquid crystal display devices, mainly polarizing plates, various optical films for touch panels, various optical films for electronic paper, various optical films for organic electroluminescence (EL) displays, and the like. In addition, the pressure-sensitive adhesive layer may be laminated on at least one surface of these optical films to form an optical film with a pressure-sensitive adhesive layer.Specific examples of the optical film include structures such as "optical film / pressure-sensitive adhesive layer / optical film", "optical film / pressure-sensitive adhesive layer / release film", "optical film / pressure-sensitive adhesive layer", "optical film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / optical film", "optical film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / release film", and "release film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / release film". For example, in the case of "optical film / adhesive layer / release film" having an adhesive layer protected by a release film, the release film can be peeled off to expose the adhesive layer as in "optical film / adhesive layer", and then laminated with another optical film, thereby obtaining a configuration such as "optical film / adhesive layer / optical film" in which the adhesive layer is used for interlayer bonding. EXAMPLES

[0044] The present invention will now be described in detail with reference to examples.

[0045] <Production of Acrylic Copolymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 90 parts by weight of butyl acrylate, 10 parts by weight of benzyl acrylate, 10 parts by weight of N-vinylpyrrolidone, 2.5 parts by weight of 6-hydroxyhexyl acrylate, and 60 parts by weight of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic copolymer solution 1 used in Example 1 with a weight average molecular weight of 500,000. A part of the acrylic copolymer was collected and used as a sample for measuring the acid value described later. [Examples 2 to 5 and Comparative Examples 1 to 3] The acrylic copolymer solutions used in Examples 2 to 5 and Comparative Examples 1 to 3 were obtained in the same manner as the acrylic copolymer solution 1 used in Example 1, except that the monomer compositions were as shown in (A) to (D) in Table 1. Although no particular measurement results are shown, the weight average molecular weights of the copolymers contained in the acrylic copolymer solutions of Examples 2 to 5 and Comparative Examples 1 to 3 were in the range of 200,000 to 2,000,000.

[0046] <Production of Pressure-Sensitive Adhesive Composition, Pressure-Sensitive Adhesive Layer, and Pressure-Sensitive Adhesive Film> [Example 1] To the acrylic copolymer solution 1 of Example 1 produced as described above, 0.5 parts by weight of Coronate HX (isocyanurate of hexamethylene diisocyanate compound) was added and stirred to obtain an adhesive composition of Example 1. This adhesive composition was applied onto a release film made of a silicone resin-coated polyethylene terephthalate (PET) film, and then dried at 90°C to remove the solvent, followed by aging for 7 days in an atmosphere of 23°C and 50% RH to obtain an adhesive film of Example 1 having an adhesive layer formed by crosslinking the adhesive composition on one side of the release film. [Examples 2 to 5 and Comparative Examples 1 to 3] PSA films of Examples 2 to 5 and Comparative Examples 1 to 3 were obtained in the same manner as the PSA film of Example 1 above, except that the compositions of the additives were as shown in Table 1 (E) and (F), respectively.

[0047] [Table 1]

[0048] In Table 1, the addition ratios of groups (C) through (F) are shown in parentheses with the total of groups (A) and (B) taken as 100 parts by weight, with the weight parts enclosed in parentheses. However, in Example 3, the total of groups (A) and (B) is 110 parts by weight, in Example 5, the total of groups (A) and (B) is 90 parts by weight, and in Comparative Example 2, the total of groups (A) and (C) is 100 parts by weight. The compound names of the abbreviations of each component used in Table 1 are shown in Table 2. Coronate (registered trademark) HX, HL, and L-45 are product names of Nippon Polyurethane Industry Co., Ltd., and D-110N is a product name of Mitsui Chemicals, Inc. HDI means hexamethylene diisocyanate, TDI means tolylene diisocyanate, and XDI means xylylene diisocyanate.

[0049] [Table 2]

[0050] <Test methods and evaluation> The release film (silicone resin-coated PET film) was peeled off from the pressure-sensitive adhesive film in Examples 1 to 5 and Comparative Examples 1 to 3 to expose the pressure-sensitive adhesive layer, which was then transferred to one side of a polarizing plate (film).

[0051] <Method of measuring adhesive strength> An adhesive layer was transferred onto one surface of a polarizing plate (film) having a thickness of 180 μm to obtain an adhesive film (optical film with an adhesive layer) as a sample. The adhesive film was laminated with a pressure roll to the non-tin surface of soda lime glass that had been cleaned with acetone, and then autoclaved at 50°C, 0.5 MPa for 20 minutes. After that, the adhesive was returned to an atmosphere of 23°C and 50% RH. After 1 hour, the peel strength of the adhesive film was measured using a tensile tester in accordance with JIS Z0237 "Test method for adhesive tapes and adhesive sheets." The peel strength when peeled in a 180° direction at a speed of 300 mm / min was taken as the adhesive strength of the adhesive layer of the adhesive film.

[0052] <Gel fraction> After aging, the mass of the measurement sample before bonding to the polarizing plate was accurately measured, and it was immersed in toluene for 24 hours and then filtered through a 200-mesh wire screen. The filtered material was then dried at 100°C for 1 hour, and the mass of the residue was accurately measured to calculate the gel fraction of the adhesive layer (adhesive after crosslinking) using the following formula. Gel fraction (%) = insoluble portion mass (g) / adhesive mass (g) × 100

[0053] <Adhesion test method> After measuring the adhesive strength, the adhesive layer of the adhesive film sample was visually inspected, and the adhesion was judged based on the state in which the base layer fell off from the polarizing plate (film). ◯: None of the adhesive layer fell off from the base layer. △: Part of the adhesive layer has lifted off from the base layer and fallen off. × The adhesive layer has fallen off from the base layer and transferred to the glass substrate.

[0054] <Reworkability> A 10 cm square adhesive film prepared in the same manner as in the adhesive strength measurement was attached to the non-tin side of soda-lime glass in the same manner to create a sample.The sample was then left in a dry atmosphere at 70°C for 24 hours, then taken out to room temperature, and the adhesive film was peeled off from the glass plate, and the adhesive residue on the surface of the adherend was visually checked. ○ No adhesive residue is observed. △: A small amount of glue residue was observed. ×: Glue residue was clearly visible.

[0055] <Durability test method> A 10 cm square adhesive film prepared in the same manner as in measuring the adhesive strength was attached to the non-tin side of soda-lime glass in the same manner to create a sample.The sample was then left in an atmosphere of 60°C and 90% RH for 250 hours, then removed from the sample and placed in an atmosphere of 23°C and 50% RH. After 1 hour, the condition of the adhesive film was visually observed to determine its durability. ○ The adhesive film does not peel off or foam at all. △: Peeling and bubbling have occurred in some parts of the adhesive film. × Peeling and bubbling have occurred over the entire adhesive film.

[0056] <Method of measuring refractive index> The refractive index of the adhesive layer at 23° C. is measured using an Abbe refractometer (manufacturer: ERMA, model: ER-2S).

[0057] <Method of measuring surface resistivity> After aging and before bonding to a polarizing plate, the release film (a silicone resin-coated PET film) was peeled off to expose the adhesive layer, and the surface resistivity of the adhesive layer was measured using a resistivity meter, Hiresta UP-HT450 (manufactured by Mitsubishi Chemical Analytech).

[0058] The evaluation results are shown in Table 3. The surface resistivity is expressed as "m×10 +n " is expressed as "mE+n" (where m is any real value and n is a positive integer).

[0059] [Table 3]

[0060] The adhesive films of Examples 1 to 5 had an initial adhesive strength of 3.0 N / 25 mm or more for a 20 μm thick adhesive layer, a refractive index of the adhesive layer within the range of 1.47 to 1.50, and were also excellent in adhesion, reworkability, and durability. In other words, the adhesive films of Examples 1 to 5 were able to overcome the requirements and problems. In addition, the adhesive films of Examples 3 to 5 had a 5.0×10 +10 It has a surface resistivity of Ω / □ or less.

[0061] The adhesive film of Comparative Example 1 had a high gel fraction and a low initial adhesive strength of the adhesive layer with a thickness of 20 μm. In addition, since it did not contain a (meth)acrylate monomer having an aromatic group, the adhesive layer had a low refractive index. In addition, the adhesive film was also poor in adhesion and durability. The adhesive film of Comparative Example 2 had a low gel fraction and a 5 μm thick adhesive layer with a low adhesive strength. In addition, since it did not contain a (meth)acrylate monomer having an aromatic group, the adhesive layer had a low refractive index. In addition, the adhesive film was also poor in adhesion, reworkability, and durability. The adhesive film of Comparative Example 3 had a low gel fraction and was also poor in reworkability and durability. As described above, the pressure-sensitive adhesive films of Comparative Examples 1 to 3 were unable to overcome the conventional requirements and problems.

Claims

1. In a pressure-sensitive adhesive layer obtained by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer, The acrylic polymer is (A) 70 to 95 parts by weight of at least one alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14; (B) 5 to 30 parts by weight of at least one (meth)acrylate monomer having an aromatic group, and, relative to a total of 100 parts by weight of the above, as other copolymerizable monomers, (C) 100 / 11 parts by weight or more and 200 / 9 parts by weight or less of at least one vinyl monomer having a nitrogen atom and no hydroxyl group; (D) 0.1 to 10 parts by weight of at least one copolymerizable vinyl monomer having a hydroxyl group, It is a copolymer having a weight average molecular weight of 200,000 to 2,000,000 that is copolymerized without containing a copolymerizable vinyl monomer having a carboxyl group, the (D) copolymerizable vinyl monomer having a hydroxyl group is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide, a crosslinking agent for crosslinking the pressure-sensitive adhesive composition is a trifunctional isocyanate compound, the pressure-sensitive adhesive layer has a thickness of 1 μm to 20 μm, and when the thickness is 20 μm, the initial adhesive strength after lamination is 3.0 (N / 25 mm) or more, and the refractive index is 1.47 to 1.50, The initial adhesive strength is a value measured by the following adhesive strength measurement method, The pressure-sensitive adhesive layer has a gel fraction of 50 to 70%. [Method for measuring adhesive strength] The adhesive layer to be measured was transferred to one side of a polarizing plate (film) having a thickness of 180 μm to obtain an adhesive film, and the obtained adhesive film was laminated with a pressure roller to the non-tin side of soda-lime glass that had been washed with acetone, and autoclaved under conditions of 50°C, 0.5 MPa x 20 minutes. After that, the adhesive film was returned to an atmosphere of 23°C x 50% RH for 1 hour, and the peel strength of the adhesive film was measured in accordance with JIS Z0237 "Test methods for adhesive tapes and adhesive sheets" and peeled at a speed of 300 mm / min in the 180° direction using a tensile tester, and this peel strength was taken as the adhesive strength.

2. The pressure-sensitive adhesive composition contains 0.1 to 5.0 parts by weight of an ionic compound having a melting point of 25 to 50° C., and the surface resistivity of the pressure-sensitive adhesive layer is 5.0×10 +10 The pressure-sensitive adhesive layer according to claim 1, characterized in that it has a resistance of Ω / □ or less.

3. 3. A pressure-sensitive adhesive film comprising the pressure-sensitive adhesive layer according to claim 1 or 2 formed on one side of a release film, and having a structure of release film / pressure-sensitive adhesive layer / release film.

4. 3. A pressure-sensitive adhesive film comprising the pressure-sensitive adhesive layer according to claim 1 or 2 laminated on one surface of a substrate.

5. 3. An optical film with a pressure-sensitive adhesive layer, comprising an optical film and the pressure-sensitive adhesive layer according to claim 1 laminated on at least one surface of the optical film.

Citation Information

Patent Citations

  • Optical component and projector

    JP2006293281A

  • Adhesive composition for optics, adhesive layer for optics, optical member with adhesive layer, method for producing the same and image display device

    JP2007084762A

  • Adhesive composition and laminate obtained by using the same

    JP2009091522A

  • Light scattering adhesive composition, light scattering adhesive layer, light scattering adhesive sheet, and backlight system using those

    JP2009209329A

  • Pressure-sensitive adhesive composition for optical films, pressure-sensitive adhesive optical film and image display

    JP2009215528A